The Influence of Motivation and Workload on Employee Performance at the Manukan Kulon Subdistrict Office, Tandes District, Surabaya City: PENGARUH MOTIVASI DAN BEBAN KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR KELURAHAN MANUKAN KULON KECAMATAN TANDES KOTA SURABAYA - Dwi Hariyono; Dewie Tri Wijayati Wardoyo; Anang Kistyanto (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
The purpose of this research is to determine the effect of motivation and workload on employee performance at the Manukan Kulon Subdistrict Office. This research includes quantitative research. The population of this study were Manukan Kulon sub-district office employees with the sampling technique used in the form of a census so that the sample in this study was all 23 Manukan Kulon sub-district office employees. The data in this research was obtained through questionnaires to respondents. The data analysis techniques used are the classical assumption test, the coefficient of determination test (R-Square), overall hypothesis testing, and individual hypothesis testing. The results of research based on multiple linear regression analysis concluded that motivation has a significant positive effect on employee performance as indicated by a regression coefficient value of 0.257 with a significance value of Sig t=0.000 and α=0.05. Workload does not have a significant effect on employee performance as indicated by t = -1822 > t table = 2.06866 (df=23, α/2=0.025), the significance value is Sig t=0.083 with α=0.05. Based on multiple linear regression analysis, the calculated F value = 12,119> F table = 3.42 (df1=2, df2=23, α=0.05), with a significance value of F = 0.000 < α=0.05, then H0 is rejected, so motivation and workload simultaneously have a significant effect on employee performance. Thus, it can be concluded that the performance of Manukan Kulon District Office employees is influenced by motivation and workload simultaneously by 58.4% and the remaining 42.6% is influenced by other factors.